Design and focus group evaluation of a bed-integrated weight measurement system for wheelchair users. Issue 4 (1st October 2016) - Mhatre, Anand; Duvall, Jonathan; Ding, Dan; Cooper, Rory; Pearlman, Jon
ABSTRACT: Regular weight monitoring is known to help with weight management, which is an important part of maintaining a healthy, active lifestyle. Unfortunately, weight monitoring is challenging for wheelchair users because the few scales that are available are expensive and very large. Consequently, wheelchair users typically learn their weight at infrequent visits to their healthcare providers, which likely contributes to higher prevalence of obesity-related health risks among this population. In this article, we describe the design and development of the Embedded Scale, or E-Scale, which is a bed-integrated bodyweight measuring system that allows a user to measure and track their weight. The E-Scale team followed a standard product development approach to build the E-Scale prototype. Bench testing results indicate that the performance of the prototype is on par with commercially available wheelchair scales (capacity = 1, 200 lbs, accuracy = 1.73 lbs, and precision = ± 0.35 lbs over one-fourth rated capacity). Institutional Review Board (IRB)-approved focus groups with 20 Veterans who use wheelchairs for mobility were conducted to gather feedback about the design, which was very positive. Development and testing results suggests the E-Scale technology is feasible and may provide a valuable tool to help wheelchair users manage their weight.